Analisis miskonsepsi materi buku pelajaran biologi kelas X untuk Sekolah Menengah Atas - Yeni Suryaningsih; Abdur Rasyid; Nia Naimatul Robi’ah (Papanda Journal of Mathematics and Science Research, 2026)
Misconceptions refer to understandings of concepts that are inconsistent with scientifically accepted explanations and may hinder the learning process in science education. One potential source of misconceptions is the use of textbooks in classroom instruction. This study aims to analyze the types and percentages of misconceptions found in senior high school Grade X biology textbooks. The research employed a descriptive qualitative approach using content analysis to examine several widely used biology textbooks. Data were collected through document analysis by identifying key biological concepts and comparing them with scientifically accurate references. The results revealed that misconceptions were found in seven main topics, namely the scope of biology, levels of biological organization, ecosystems, biodiversity, classification of living organisms, viruses, and environmental conservation. The highest percentage of misconceptions was found in the ecosystem topic (25%), followed by levels of biological organization (22%) and the scope of biology (18%), while the lowest percentage was observed in environmental conservation (4%). The identified misconceptions included incorrect definitions, improper conceptual hierarchies, misleading illustrations, and deviations from scientific principles. These findings highlight the importance of regular evaluation and careful selection of biology textbooks to ensure conceptual accuracy and support meaningful learning